Inspired lounge david grass chair using plywood / Muhamad Shahrul Elmie Mohd Sabri - Mohd Sabri, Muhamad Shahrul Elmie (2020)
Nowadays, raw materials are one of major issues in furniture industry due to the depletion of solid wood and High then price of panel products. This paper was analysed a successful inspired Lounge David Grass chair using plywood, to overcome the problem in producing strong and high quality furniture but in low manufacturing cost. The parameter of this study was, to produce and study the potential of Inspired Lounge David Grass chair by using plywood. In previous study, Lounge David Grass chair was produced by using cardboard. Due its low strength, the plywood has been applied to replace the cardboard. The evaluation of Inspired Lounge David Grass chair was carried out by distributed a set of questionnaires survey to 200 correspondents and were categorized based on demographic factors such as gender, age, profession and income. The Inspired Lounge David Grass chair has been evaluated on the material used, easy to handle, unique, comfortable and market value in furniture industry. There are more than 90% of correspondents agree and give positive feedback on Inspired Lounge David Grass chair by using plywood. Overall, the correspondents satisfied that the Inspired Lounge David Grass chair has good potential in the furniture market due its design, strength and price.